CD70 Exacerbates Blood Pressure Elevation and Renal Damage in Response to Repeated Hypertensive Stimuli. Issue 8 (15th April 2016) - Itani, Hana A.; Xiao, Liang; Saleh, Mohamed A.; Wu, Jing; Pilkinton, Mark A.; Dale, Bethany L.; Barbaro, Natalia R.; Foss, Jason D.; Kirabo, Annet; Montaniel, Kim R.; Norlander, Allison E.; Chen, Wei; et al.
Abstract : Rationale: : Accumulating evidence supports a role of adaptive immunity and particularly T cells in the pathogenesis of hypertension. Formation of memory T cells, which requires the costimulatory molecule CD70 on antigen-presenting cells, is a cardinal feature of adaptive immunity. Objective: : To test the hypothesis that CD70 and immunologic memory contribute to the blood pressure elevation and renal dysfunction mediated by repeated hypertensive challenges. Methods and Results: : We imposed repeated hypertensive challenges using either N ω -nitro-L-arginine methyl ester hydrochloride (L-NAME)/high salt or repeated angiotensin II stimulation in mice. During these challenges effector memory T cells (T EM ) accumulated in the kidney and bone marrow. In the L-NAME/high-salt model, memory T cells of the kidney were predominant sources of interferon-γ and interleukin-17A, known to contribute to hypertension. L-NAME/high salt increased macrophage and dendritic cell surface expression of CD70 by 3- to 5-fold. Mice lacking CD70 did not accumulate T EM cells and did not develop hypertension to either high salt or the second angiotensin II challenge and were protected against renal damage. Bone marrow–residing T EM cells proliferated and redistributed to the kidney in response to repeated salt feeding. Adoptively transferred T EM cells from hypertensive mice homed to the bone marrow and spleen and expanded on salt feeding of the recipient mice. Conclusions: : Our findings illustrate a previously undefined role of CD70 and long-lived T EM cells in the development of blood pressure elevation and end-organ damage that occur on delayed exposure to mild hypertensive stimuli. Interventions to prevent repeated hypertensive surges could attenuate formation of hypertension-specific T EM cells. Abstract : Supplemental Digital Content is available in the text.